PERSEPSI MASYARAKAT TERHADAP IMPLEMENTASI METODE PEMBAYARAN MENGGUNAKAN KARTU E-MONEY (BRIZZI) PADA BUS TRANS PADANG - Syamsu J; Dian Oldisan; Yurismen Efendi (Jurnal Public Administration, Business and Rural Development Planning, 2022)
This study aims to analyze and evaluate public perceptions of the use of the BRIZZI e-money card on the Trans Padang Bus as a means of payment. Since it was socialized and implemented in 2019, the use of BRIZZI e-money has been implemented and used as a means of payment for public transportation for the Trans Padang Bus, but there are still some passengers who have difficulty making payments such as not having a BRIZZI e-money card or balance in an e-card. - empty BRIZZI money. This research method uses descriptive. Data collection tools using interviews and observations of 36 informants consisting of 30 passengers and 6 people who are Trans Padang Bus stewards. The results of data analysis show that the public has a positive perception of the use of this BRIZZI e-money card as a means of payment on the Trans Padang Bus. Their positive perception is seen from the factors of convenience, benefits, and security. However, negative perceptions are also directed at passengers with certain characteristics such as elderly passengers who find it difficult to use BRIZZI e-money and also passengers who rarely use public transportation on the Trans Padang Bus, so they feel that having BRIZZI e-money is not something that is useful for them considering that its use is only for payments for Trans Padang buses.